Factors causing low pass rate in biology at ordinary level in Zhombe circuit - Muyambo, Tafadzwa (Midlands State University, 2018)
The study sought to establish the factors causing low pass rate in Biology in Zhombe circuit. A qualitative research design was used which enabled the researcher to explore human behaviour that cannot be quantified. It also enabled me to understand factors causing low pass rate from a holistic view point because it employs a wide variety of methods in its enquiry. Purposive sampling was used to select heads of departments and biology teachers while stratified random sampling was used to select the students. Data was generated using semi-structured interviews, observations guide, as well as document analysis. The research study has revealed that low pass rate in biology is caused by many factors which include lack of experienced teachers and shortage of resources among other factors. The study recommends in service training of teachers to equip them with effective child centred approaches of teaching and fund raising activities to raise funds that can be used to buy the teaching and learning resources.